TIMBER-CONCRETE COMPOSITE RIBBED SLABS WITH HIGH-PERFORMANCE FIBRE-CONCRETE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Composite of such renewable material as timber and the most popular man-made material as concrete offers many benefits. Such of them are high load-bearing capacity with low dead load and increased structural bending stiffness. Higher specific strength of high-performance concrete in comparison with ordinary concrete ensures more efficient use of the material. Addition of fibres can reduce the fragility and autogenous shrinkage cracks of high-performance concrete and makes it possible to design thinner layers of concrete for timber-concrete composite structures. Ribbed slabs as solution for the floor slabs, allows to reduce material consumption and to integrate engineering communications into the structures. The current study focuses on determining the effect of the use of high-performance fibre reinforced concrete for timber-concrete composite ribbed slabs with adhesive connection between layers, as the most effective connection type for composite action. The effect of the use of high-performance fibre reinforced concrete is determined by comparison of mid-span displacements of the ribbed slabs numerical models. Three-dimensional finite element models of timber and ordinary concrete composite ribbed slab and high-performance fibre reinforced concrete with additional longitudinal reinforcement ribbed slab are validated by experiment data. Developed numerical models makes it possible to predict the dependence of applied load on mid-span displacement in three-point bending with sufficient precision. Obtained results showed, that replacement of ordinary concrete layer by high-performance fibre reinforced concrete in timber-concrete composite ribbed slab with adhesive connection up to 1.68 times decrease vertical mid-span displacements.